PENGARUH MODEL PEMBELAJARAN LOGAN AVENUE PROBLEM SOLVING (LAPS) – HEURISTIK TERHADAP CIVIC KNOWLEDGE SISWA (STUDI PADA KELAS X SMA NEGERI 1 NGEMPLAK TAHUN PELAJARAN 2016/2017) - Arifah, Ukti Binti, Triyanto, Winarno (Prodi PPKn FKIP UNS, 2017)
ABSTRACT The purpose of this research was to find out the effect of Logan Avenue Problem Solving (LAPS)-Heuristik learning model on students? civic knowledge (a study to tenth grade students of SMAN 1 Ngemplak 2016/2017 academic year), especially in basic competence 3.7 Interpreting the importance of Archipelago Concept in the Context of Republic of Indonesia State.The method of this research was true experimental design with posttest only control design. The data were collected through document analysis, observation, and objective test. The analysis prerequisite test in this research was carried out by using normality and homogeneity tests.The data were analyzed quantitatively by using t-test.The result of this research showed that the mean of students? civic knowledge test was 85.4358 for experiment gruop and 79.6667 for control group. The result of t-test showed tstatistic>ttableor 3.2612 > 1.9908 at significance level of 5% so, Howas rejected andHa was accepted. In other words, the class taught by using LAPS- heuristic learning model was better than the one with conventional learning model. Based on that description, it can be concluded that LAPS- heuristic learning model affects significantly to the students? civic knowledge (a study to tenth grade students of SMAN 1 Ngemplak 2016/2017 academic year), especially in basic competence 3.7 Interpreting the importance of Archipelago Concept in the Context of Republic of Indonesia State.Keywords: Logan Avenue Problem Solving (LAPS)-Heuristic learning model, students?civic knowledge.